2021
DOI: 10.4085/1062-6050-611-20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries in National Collegiate Athletic Association Men's Ice Hockey: 2014–2015 Through 2018–2019

Abstract: Context The National Collegiate Athletic Association has supported men's ice hockey, a distinct sport that mandates high-velocity gamesmanship, since 1974. Background Injury surveillance systems are designed to identify evolving injury trends and their temporal qualities. Continual monitoring of collegiate men's ice hockey athletes remains essential. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These athletes are also more likely to experience more severe symptoms and can take longer to recover 9. NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females 56–59. However, one US collegiate study found higher match SRC rates for females than males in each of these sports 35.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These athletes are also more likely to experience more severe symptoms and can take longer to recover 9. NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females 56–59. However, one US collegiate study found higher match SRC rates for females than males in each of these sports 35.…”
Section: Discussionsupporting
confidence: 70%
“…9 NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females. [56][57][58][59] However, one US collegiate study found higher match SRC rates for females than males in each of these sports. 35 A systematic review of SRCs in team contact sports also reported far lower match rates for male rugby union (2.16-8.93 per 1000 AE hours) than reported for females in the current study.…”
Section: Open Accessmentioning
confidence: 99%
“…Because there are certainly patients with minor injuries that are treated in the emergency department and then discharged, or patients who are admitted to non-trauma centers, this study does not capture the full spectrum of injuries sustained while playing hockey. There are NCAA-based data suggesting that the majority of hockey injuries in both men and women are contusions, sprains, and strains, 23,24 which highlight the likelihood of these minor injuries evading capture by the current study. Furthermore, approximately onethird of the burden of injury following ice hockey appears to be related to overuse injuries, 25 which would be unlikely to be captured by this study which examines admission to acute care hospitals.…”
Section: Discussionmentioning
confidence: 75%
“…Over the study period, there were 306 patients with hockey-related injuries (<1% of all patients in the NTDB). The median age was 15 [13][14][15][16][17][18][19][20][21][22][23][24][25] years and ranged from 5 to 71 years (Table 1). The majority of patients were male (n = 279, 91%).…”
Section: Patient Demographics Clinical Data and Injury Datamentioning
confidence: 99%
“…3 Furthermore, during the 2014-15 to the 2018-19 collegiate hockey seasons, injuries to the hip and groin constituted the body region with the highest proportion (~20%) of injuries sustained during practice. 4 However, it is important to note that the majority of these (~50-60%) do not cause time-loss from training or competition. 5,6 Nonetheless, on-going hip and groin pain can have debilitating long-term effects, such as increased depen-dency on medication, higher surgical intervention rates, and potentially early retirement.…”
Section: Introductionmentioning
confidence: 99%